2014
DOI: 10.1111/cen.12471
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular disorders in euthyroid patients with Hashimoto's thyroiditis: role of thyroid autoimmunity

Abstract: In euthyroid HT patients, a significant relationship between subclinical vestibular damage and the degree of TPOAb titre was documented. This finding suggests that circulating antithyroid autoantibodies may represent a risk factor for developing vestibular dysfunction. An accurate vestibular evaluation of HT patients with or without symptoms is therefore warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 31 publications
2
19
0
2
Order By: Relevance
“…Mechanical movements of thyroid autoantibodies in the inner ear fluid or the development of autoimmune microangiitis in the labyrinth can result in BPPV in the presence of hyperthyroidism or hypothyroidism 51. Other studies support a role for thyroid hormone fluctuations52 and circulating anti-thyroid autoantibodies53 related to vestibular dysfunction in subsequent BPPV development. Therefore, dysregulation of the immune system may play a vital role between hyperthyroidism and BPPV as documented by our study.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical movements of thyroid autoantibodies in the inner ear fluid or the development of autoimmune microangiitis in the labyrinth can result in BPPV in the presence of hyperthyroidism or hypothyroidism 51. Other studies support a role for thyroid hormone fluctuations52 and circulating anti-thyroid autoantibodies53 related to vestibular dysfunction in subsequent BPPV development. Therefore, dysregulation of the immune system may play a vital role between hyperthyroidism and BPPV as documented by our study.…”
Section: Discussionmentioning
confidence: 99%
“…HT is also related to dysfunction of the vestibular system, which can be identified by abnormal caloric test and vestibular-evoked myogenic potential. The dysfunction was linked to increased anti-TPO antibodies without identification of the pathogenic mechanism (124). …”
Section: Anti-thyroid Antibody Types: the Key To The Diagnosismentioning
confidence: 99%
“…Although these abnormalities can occur as a direct consequence of hypothyroidism [1], it has been suggested that the circulating antithyroid autoantibodies can lead to T-cell mediated vestibulocochlear dysfunction. A review of the literature shows various case studies documenting the association of these two autoimmune entities [1215] which demonstrate the existence of a clear relationship between thyroid autoimmunity and the inner ear damage, regardless of thyroid function. Furthermore, it is postulated that the immune complexes precipitation in the inner ear with concomitant autoimmune inflammation may be the pathogenic mechanism shared with HT.…”
Section: Discussionmentioning
confidence: 99%